2010
DOI: 10.1166/jnn.2010.2882
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fe Content in Electrodeposited CoFe/Cu Multilayers on Structural, Magnetic and Magnetoresistance Characterizations

Abstract: A series of CoFe/Cu multilayers were electrodeposited on Ti substrates from the electrolytes containing their metal ion under potentiostatic control, but the Fe concentration in the electrolytes was changed from 0.0125 M to 0.2 M. The deposition was carried out in a three-electrode cell at room temperature. The deposition of Cu layers was made at a cathode potential of -0.3 V with respect to saturated calomel electrode (SCE), while the ferromagnetic CoFe layers were deposited at -1.5 V versus SCE. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
4
18
1
Order By: Relevance
“…However, the decrease reported by Tekgül et al 10 is much slower than that was observed in the present study. The reported MR values are also higher.…”
Section: Comparison Of Gmr Behavior With Previously Investigated Ed Fcontrasting
confidence: 76%
See 4 more Smart Citations
“…However, the decrease reported by Tekgül et al 10 is much slower than that was observed in the present study. The reported MR values are also higher.…”
Section: Comparison Of Gmr Behavior With Previously Investigated Ed Fcontrasting
confidence: 76%
“…The preset nominal Co-Fe and Cu layer thicknesses were kept constant at 6 nm and 4.5 nm, respectively. The applied deposition potentials were E FeCo (SCE) = −1.5 V and E Cu (SCE) = −0.3 V. The Cu deposition potential is even more positive than the one used by Kakuno et al; 9 therefore, an even stronger dissolution of the magnetic layer and, thus, even larger layer thickness changes with respect to the nominal values can be expected for the multilayers investigated by Tekgül et al 10 These authors have also analyzed their multilayers and the resulting Fe/Co ratios in their magnetic layers with varying Fe concentrations in the bath exhibit a fairly good agreement with our data as shown in Fig. 4 (although the comparison may not be completely valid since the current density used in their work for magnetic layer deposition is not known).…”
Section: Comparison Of Gmr Behavior With Previously Investigated Ed Fmentioning
confidence: 83%
See 3 more Smart Citations